Análise do iGovContrat/2018 - índice de governança e gestão em contratações da Universidade Federal do Paraná e proposições para melhorar o índice - Pierini, Erika Kakinohana (2020)
The Federal Court of Accounts carries out na annual survey of Governance and Management applied to Federal Public Organizations in the most diverse áreas, including Federal Education Institutions. Through this survey, TCU monitors the iGG Integrated Governance and Management índex with an approach in four áreas: Governance, IT Management, People Management and Contract Management. This paper addresses the iGovContrat/2018 – Governance and Management índex in hiringat the Federal University of Paraná. This study deals with the examination of the TCU governance model that guided the structuring of the questionnaire used in the survey, and the level of adoption of good practices in the acquisition of assets and contracting services from UFPR based on the survey of the scores for each variable. The methodological approach is characterized by the explanatory descriptive nature, outlined in a case study, with tchnical procedures for bibliographic and documentary research. A bibliographic analysis was also carried out according to the ProKnow-C method and using the Zotero software as a manager application for surveys carried out on the theme “governance index”.To obtain the score of the variables that make up the índex, the program SPSS – Statistical Package for the Social Sciences, and Excel was used. As a result, we highlilght the exposure of the main conceptual approaches to public governance; the concept of governance that supports the survey carried out by TCU; and finally the analysis of the variables that resulted in UFPR’s iGovContrat/2018, and comparatively the changes in the questionnaire/2020, in order to identify the weaknesses and priorities of action in the strategic actions that contribute to the improving of the índex.